Sexual modulation in a polyploid grass: a reproductive contest between environmentally inducible sexual and genetically dominant apomictic pathways - Karunarathne, Piyal (2020)
In systems alternating between sexual and asexual reproduction, sex increases under unfavorable environmental conditions. In plants producing sexual and asexual (apomictic) seeds, studies on the influence of environmental factors on sex are equivocal. We used Paspalum intermedium to study environmental effects on the expression of sexual and apomictic developments, and on resulting reproductive fitness variables. Flow cytometric and embryological analyses were performed to characterize ploidy and reproductive modes, and effects of local climatic conditions on sexual and apomictic ovule and seed frequencies were determined. Seed set and germination data were collected and used to estimate reproductive fitness. Frequencies of sexual and apomictic ovules and seeds were highly variable within and among populations. Apomictic development exhibited higher competitive ability but lower overall fitness. Frequencies of sexual reproduction in facultative apomictic plants increased at lower temperatures and wider mean diurnal temperature ranges. We identified a twofold higher fitness advantage of sexuality and a Tug of War between factors intrinsic to apomixis and environmental stressors promoting sexuality which influence the distribution of sex in apomictic populations. This points toward a crucial role of local ecological conditions in promoting a reshuffling of genetic variability that may be shaping the adaptative landscape in apomictic P. intermedium plants.